Rastreamento de variantes genéticas em DNA polimerases com atividade translesão na neoplasia mielodisplástica - Oliveira, Roberta Tatiane Germano de (2023)
Myelodysplastic Neoplasms (MDS) is the most common bone marrow cancer in the elderly over 65 years, characterized by cytopenias, cell dysplasias, ineffective hematopoiesis, and risk of progression to acute myeloid leukemia. Cytogenetic alterations are present in 40-60% of cases and 94% of patients have at least one oncogenic mutation. These changes are believed to be due to DNA damage caused by endogenous oxidative processes or environmental exposure. Tolerance to non-repairable DNA damage is performed by translesion synthesis DNA polymerases (TLS), which pierce or correct the lesions; however, they can generate point mutations, and their study is important in oncological diseases. The aim of this study was to carry out a genetic screening to identify, characterize and classify variants in DNA polymerase genes with TLS activity (REV3L, POLQ, REV1, POLI, POLH, POLK, POLL, and POLN) in patients with MDS, relating the findings with chromosomal alterations and disease subtypes of lower and higher risk of progression to AML. Bone marrow samples from 50 patients diagnosed with MDS were sequenced by NGS-Illumina, with 17 classified as MDS with excess blasts (SMD-EB) and 13 classified as MDS with ring sideroblasts (SMD-SA). The cytogenetic study was performed for the prognostic characterization of the patients. For the analysis of the variants obtained, five in silico pathogenicity prediction tools were used (Ensembl VEP, Mutation Taster, Sift, Mutpred, and Provean) and, for the oncogenicity analysis of these variants, standards for classification of oncogenicity of somatic variants (SOP), recommended by the Clinical Genome Resource (ClinGen), Cancer Genomics Consortium (CGC) and Variant Interpretation for Cancer Consortium (VICC). This study selected Loss-of-function (LoF) variants registered in the COSMIC Database for oncogenicity classification. For the POLQ gene, 194 variants, 85 missense variants, 38 synonymous variants, and 17 loss-of-function variants (Lof - frameshift, inframe, stop gained, stop loss, splice donor, and splice acceptor) were identified. Of the analyzed variants, 10 were classified as VUS and 1 as Probably Benign. For the REV3L gene, 284 variants were identified (85 missense, 38 synonyms, and 17 with loss of function). Of the analyzed variants, 18 were classified as Potentially Oncogenic, 7 as VUS, and 3 as Benign. For the POLI gene, 58 variants were identified (22 missense, 7 synonyms, and 17 with loss of function. Of the analyzed variants, 3 were classified as Potentially Oncogenic, 1 as VUS, and 2 as Benign or Probably Benign. For the REV1 gene, 108 variants were identified (39 missense, 12 synonyms, and 8 with loss of function. Of the analyzed variants, 2 were classified as Potentially Oncogenic and 4 as VUS. For the POLH gene, 22 variants were identified (18 missense and 4 synonyms). We did not identify oncogenic variants in the gene POLH. Patients of the SMD-EB subtype had a high incidence of LoF variants in the POLQ and REV3L genes, compared to patients of the SMD-SA subtype, representing loss of the translesion synthesis mechanism in these patients. Patients of the SMD-SA subtype with normal karyotype had less frequency of LoF variants and higher frequency of missense variants for the REV1 and POLI genes, as well as high rates of non-LoF variants, which may represent a biomarker of genomic instability in MDS. A patient with a complex karyotype showed an accumulation of LoF mutations in the POLQ and REV3L genes, which suggests that the great genetic instability observed in patients with multiple chromosomal alterations may be present due to the absence of the TLS mechanism. These results reinforce the impact of genetic mutations on the pathophysiological process of MDS, especially affecting genes not included in current prognostic risk scores.